Physician Characteristics Strongly Predict Patient Enrollment in Hospice - Obermeyer, Ziad (Health Aff (Millwood), 2015)
Individual physicians are widely believed to play a large role in patients’ decisions about end-of-life care, but little empirical evidence supports this view. We developed a novel method for measuring the relationship between physicians’ characteristics and hospice enrollment in a nationally representative sample of Medicare patients with poor-prognosis cancer—for whom palliative treatment and hospice would be considered standard of care—who died in the period 2006–11. We found that the proportion of a physician’s patients that were enrolled in hospice was a strong predictor of whether or not their other patients would enroll in hospice. The magnitude of this association was larger than that of other known predictors of hospice enrollment that we examined, including patient medical comorbidity, age, race, and sex. Patients cared for by medical oncologists, and those cared for in not-for-profit hospitals, were significantly more likely to enroll in hospice than other patients. These findings suggest that physician characteristics are one of the strongest predictors of whether a patient receives hospice care—which mounting evidence indicates can improve care quality and reduce costs. Interventions geared toward physicians, both by specialty and by previous history of patients’ hospice enrollment, may help optimize appropriate hospice use.